Evaluation of biocontrol potential of thermotolerant Trichoderma and Pseudomonas against seed and soil borne diseases of safflower: EVALUATION OF TRICHODERMA AND PSEUDOMONAS AGAINST SEED AND SOIL BORNE DISEASES - D R MURUMKAR; D V INDI; R D PRASAD; S K SHINDE (Journal of Oilseeds Research, 2018)
A field experiment was conducted for two consecutive rabi seasons from 2012-13 to 2013-14 to evaluate the biocontrol potential of a thermotolerant Trichoderma strain (Th4d) and a Pseudomonas strain (P1) as seed dressers for management of seed and soil borne diseases of safflower. Among different seed treatments, carbendazim 50% WP @ 2g/kg seed recorded the least incidence of Macrophomina root rot (7.71%), Fusarium wilt (9.50%) and Phytophthora seedling blight (12.05%) followed by Trichoderma harzianum Th4d SC @ 2ml/kg seed (8.84%, 11.09% and 14.95%), Trichoderma harzianum Th4d WP @ 10g/kg seed (10.11%, 12.03% and 15.93%) and Pseudomonas sp. P1WP @ 5g/kg seed (10.59%, 12.32% and 17.07%) . Moreover, seed treatment with carbendazim 50% WP @ 2g/kg seed recorded highest seed yield (806 kg/ha) and Benefit: Cost ratio of 1.84 followed by T. harzianum Th4d SC @ 2 ml/kg seed (770 kg/ha, 1.76), T. harzianum Th4d WP @ 10g/kg seed (743 kg/ha, 1.70) and bacteria P1 WP @ 5g/kg seed (691 kg/ha, 1.58) which were statistically at par with each other. The overall results indicated that for effective and economical management of the seed/soil borne diseases of safflower and getting higher seed yield, it is recommended to treat the safflower seed before sowing with carbendazim 50% WP @ 2 g/kg or Trichoderma harzianum Th4d SC @ 2ml/kg or Trichoderma harzianum Th4d WP @ 10g/kg or Pseudomonas sp. P1 WP @ 5g/kg seed.